Streptokinase Stability Pattern during Storage in Various Solvents and at Different Temperatures - Martin, M; Technical assistance; Auel, Fräulein H (Thrombosis and Haemostasis, 1975)
The activity drop of 5 u streptokinase was measured in 1 ml each of various solutions (0.9% NaCl solution, 5% glucose solution, 5% levulose solution, 10% dextran solution, gelatin solution, 3% albumin solution, Michaelis buffer, glucose (5%)-heparin (750 u/ml) solution) at different incubation temperatures (–20° c, 4° c, 20 c, 37 C), and over different observation periods (15 min, 30 min, 45 min, 60 min, 6 h, 12 h, 24 h, and 48 h). Solution media tested for streptokinase-protecting quality were broken down into three groups.Group I: Solvents displaying excellent stabilizing properties (gelatin and albumin solutions).Group II: Solvents displaying medium stabilizing properties (dextran and levulose solutions).Group III: Solvents displaying poor stabilizing properties (NaCl and glucose solutions, Michaelis buffer).In testing streptokinase concentrations as used for therapeutic purposes (1500 u/ml, 50,000 u/ml), no decay was found to take place over observation periods of up to 48 h, and no influence by different solvents (Group I, II or III) was traceable. Heparin stored with streptokinase at room temperature over a period of 48 h did not alter the streptokinase stability.Some mechanisms concerning the stability pattern of streptokinase are discussed. It appears that low streptokinase concentrations need negatively charged colloids to keep the protein structure intact. The streptokinase-protecting macro-molecules tested so far were albumin, gelatin, and streptokinase. Obviously, streptokinase by itself was able to preserve its own stability provided its concentration was of a certain order of magnitude (1500 u/ml, 50,000 u/ml).